The identification of determinants of growth failure and focus areas for the prevention thereof in 12 to 24 month old children attending the Duncan Village Day Hospital in East London - De Villiers, Anniza (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc (Dietetics)) -- University of Stellenbosch, 1998.